Cadmium-Containing Carbonic Anhydrase CDCA1 in Marine Diatom Thalassiosira weissflogii - Vincenzo Alterio (Marine Drugs, 2015)
The Carbon Concentration Mechanism (CCM) allows phytoplakton species to accumulate the dissolved inorganic carbon (DIC) necessary for an efficient photosynthesis even under carbon dioxide limitation. In this mechanism of primary importance for diatoms, a key role is played by carbonic anhydrase (CA) enzymes which catalyze the reversible hydration of CO2, thus taking part in the acquisition of inorganic carbon for photosynthesis. A novel CA, named CDCA1, has been recently discovered in the marine diatom Thalassiosira weissflogii. CDCA1 is a cambialistic enzyme since it naturally uses Cd2+ as catalytic metal ion, but if necessary can spontaneously exchange Cd2+ to Zn2+. Here, the biochemical and structural features of CDCA1 enzyme will be presented together with its putative biotechnological applications for the detection of metal ions in seawaters.